Genetic testing and genetic counselling in hypertrophic cardiomyopathy: the French experience. Issue 10 (1st October 2002) - Charron, P; Héron, D; Gargiulo, M; Richard, P; Dubourg, O; Desnos, M; Bouhour, J-B; Feingold, J; Carrier, L; Hainque, B; Schwartz, K; Komajda, M
Abstract : Aims: A major breakthrough in the molecular genetics of hypertrophic cardiomyopathy (HCM) has made genetic testing now available in clinical practice, raising new questions about its implications, potential benefits, and the organisation of the procedure. The aim of this work was (1) to discuss the different questions related to genetic testing in HCM, and propose guidelines for the different situations, (2) to report our preliminary experience with a specific procedure. Methods and results: The main questions asked by patients and relatives concern presymptomatic diagnosis and prenatal counselling/diagnosis, while clinicians sometimes discuss diagnostic and prognostic testing. To take into account the complex medical and psychological implications of this new approach, we developed a specific, multidisciplinary, and multiple step procedure, including a cardiologist, a geneticist, and a psychologist. Seventy subjects were examined, including (1) 29 adults for presymptomatic diagnosis (of whom 10 left the procedure after the first visit and 19 continued, among whom six had a mutation and two experienced negative psychological impact, observed during follow up), (2) nine couples of parents for presymptomatic diagnosis in their children (the procedure was stopped after the first visit in eight and continued in one), (3) 22 couples for prenatal counselling (no prenatal genetic testing was asked for after the first visit), and (4) 10 subjects for diagnostic testing. We decided to perform no prognostic testing. Conclusion: Our preliminary experience confirms the complexity of the situation and suggests the necessity for a specific procedure to ensure good practice in genetic testing of HCM.